Pregnant Women’s Intentions to Implement Safety Practices for Preventing Infant Injury: A Cross-Sectional Study - Honda, Chikako (Int J Environ Res Public Health, 2020)
Injury prevention education for pregnant women may be beneficial for infants’ safety. Currently, knowledge about the scope of an expectant mother’s intent to prevent injury is limited. The objective of this study was to determine pregnant women’s intentions to implement infant injury prevention strategies. From May to June 2017, a self-administered questionnaire based on the precaution adoption process model was distributed among pregnant women who participated in a parenting preparation class in a city, Tokyo. Pregnant women’s intentions to implement the following eight kinds of safety practices were measured: three practices regarding suffocation, two regarding falls, one safety practice for burns, one for accidental ingestion, and one for traffic accidents. Among 132 respondents (response rate: 83.5%; mean age: 33.4 years; mean gestational age: 29 weeks), the most common unawareness issue was “Make sure that there is no space between the mattress and bed frame” (68.2%), followed by “Use a firm mattress or futon” (38.5%) and “Keep soft objects away from the baby’s head in the baby’s sleep area” (31.8%); 58% or more women reported having already “decided to implement” the other five practices. Safety practices that pregnant women were mostly unaware of were for preventing suffocation, despite this being a leading cause of death in terms of unintentional infant injury. In comparison, the safety practices for falls, burns, and accidental ingestion were more known to pregnant women. The pregnant women’s intention to implement injury prevention for infants varied by safety practices. These findings could be used to improve the focus of antenatal education programs for the prevention of infant injury.